KAJIAN SPASIAL DAMPAK PERUBAHAN IKLIM TERHADAP PRODUKSI PERTANIAN - Rika Harini; Bowo Susilo (Agripita: Jurnal Agribisnis dan Pembangunan Pertanian, 2017)
One of the pillars studies in sustainable development at the global level (SDGs) is a development environment. This pillar examines food security, sustainable consumption patterns and climate change. Climate change will affect agricultural activities. Climate change often causes experienced farmers crop failure because excessive rain or long summer season. The purpose of this study was to assess the effect of climate change on agricultural production. This study uses secondary data, that is rainfall data and agricultural production data as a baseline. This study examined descriptive statistics using maps, tables and graphs. The results showed a trend towards a decrease in agricultural production in all districts/cities. Based on regression analysis of the decline in agricultural production, namely cereals (rice, corn, cassava and sweet potato) is significantly influenced by changes in rainfall in all regions of the Province North Kalimantan except Tana Tindung Distict.